Report 11: How to Develop a Weighted Application Blank - Chartier, Roger (Relations industrielles / Industrial Relations, 1953)
The article briefly reviews "Report 11: How to Develop a Weighted Application Blank," by Josephine S. Welch, C. Harold Stone and Paterson, February 1952 (19 pages).